IMPLEMENTASI KEBIJAKAN KABUPATEN LAYAK ANAK (KLA) DI KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Rinawati Rinawati; Annisa Fitri (UNES Law Review, 2023)
This study aims to answer the formulation of the problem regarding how to implement child-friendly policies (KLA) in the Kinali District, West Pasaman Regency, and the importance of this policy in West Pasaman. To answer the research problem, field research was used. The method used was a qualitative method with a descriptive approach based on data collection techniques in this study including observation, interviews, and documentation. Data were analyzed namely data reduction, data presentation, and data verification or conclusion. The results of this study indicate that the successful implementation according to Edward III --namely communication, resources, disposition, and bureaucratic structure. The implementation of child-friendly districts in the Kinali sub-district is protected by legal force in the form of regional regulations and regent regulations. However, it needs to be followed by other supporting actions and policies. Because in the disposition variable as measured by the commitment of the executors, there are still deficiencies. The importance of Child-Friendly District Policies (KLA) in Kinali District, West Pasaman Regency, namely to: Carry out the Mandate of Law No. 35 of 2014 Concerning Child Protection and Fulfillment of Children's Human Rights and Providing space for children to address environmental issues where children, like adults, can be invited to cooperate and solve problems related to the environment.